Evaluation of degradation of the stability of the complex information security system in time - Журиленко, Б.Є. (Proceedings of National Aviation University, 2007)
Expression and method of calculation are got for determination of complex information defense system time probability. Penetration powers development, information reading systems development, complex information defense system elements firmness degradation are taken info account in expression.